Immunohistochemical expression of parathyroid hormone-related protein and ezrin in invasive breast carcinoma of no special type: a retrospective analysis - Menna Allah Gamil Ali Shalaby; Marwa Mohammed Dawoud; Marwa Salah Gadallah; Asmaa Gaber Abdou (Diagnostic Pathology)
Abstract Background Globally, breast cancer ranks among the most common malignancies and has a high mortality rate. Invasive breast carcinoma of no special type (IBC-NST) presents a heterogeneous group with variable prognosis. Identifying reliable biomarkers is crucial for improving treatment strategies and predicting outcomes. This study investigates the immunohistochemical expression of parathyroid hormone-related protein (PTHrP) and ezrin in IBC-NST and their correlation with clinicopathological features and overall survival. Methods This retrospective study analyzed 160 paraffin-embedded tissue samples, including 123 IBC-NST and 37 normal breast tissues, collected from patients treated at Menoufia University Hospital during the period from January 2018 to January 2022. Immunohistochemical staining for PTHrP and ezrin was performed, and expression levels were quantified using the H score. Results PTHrP expression was significantly higher in IBC-NST than in adjacent DCIS and normal tissues (p < 0.001). High PTHrP percent of expression was associated with metastasis (p = 0.009), bone metastasis (p = 0.012), and lymphovascular invasion (p = 0.037). Ezrin expression was also significantly elevated in IBC-NST, with higher H score values correlating with high tumor grade (p = 0.002), high N stage (p = 0.045), advanced AJCC stage grouping (p = 0.0043) and metastasis (p = 0.001). A significant positive correlation was observed between PTHrP and ezrin expression (rs = 0.341, p < 0.001). Kaplan-Meier analysis showed that high ezrin expression, in terms of intensity (p = 0.007) and H score (p = 0.002), was linked to poorer survival. Conclusion The study highlights the significant roles of PTHrP and ezrin in breast cancer progression. Elevated levels of these proteins are associated with more aggressive disease, suggesting their capability as prognostic indicators and treatment targets in breast cancer. Additional studies are required to investigate their interaction and collective influence on breast cancer metastasis and treatment.